2018
DOI: 10.1016/j.neuropharm.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Importance of kynurenine 3-monooxygenase for spontaneous firing and pharmacological responses of midbrain dopamine neurons: Relevance for schizophrenia

Abstract: Kynurenine 3-monooxygenase (KMO) is an essential enzyme of the kynurenine pathway, converting kynurenine into 3-hydroxykynurenine. Inhibition of KMO increases kynurenine, resulting in elevated levels of kynurenic acid (KYNA), an endogenous N-methyl-d-aspartate and α*7-nicotinic receptor antagonist. The concentration of KYNA is elevated in the brain of patients with schizophrenia, possibly as a result of a reduced KMO activity. In the present study, using in vivo single cell recording techniques, we investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 74 publications
2
22
0
1
Order By: Relevance
“…In addition, CD4+ T-cells were less proliferative in culture with VE600wt MCLs compared with VE600E MCLs, which may reflect the critical role of elevated KYNA on the induction of CD4+ T-cell exhaustion in co-culture set-up. Additionally, the lower mRNA KMO expression in CD4+ T-cells and elevated level of KYNA upon co-culture may propose KMO as an enzyme that is crucial for determining the levels of KYNA, which has also been reported elsewhere 34 .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In addition, CD4+ T-cells were less proliferative in culture with VE600wt MCLs compared with VE600E MCLs, which may reflect the critical role of elevated KYNA on the induction of CD4+ T-cell exhaustion in co-culture set-up. Additionally, the lower mRNA KMO expression in CD4+ T-cells and elevated level of KYNA upon co-culture may propose KMO as an enzyme that is crucial for determining the levels of KYNA, which has also been reported elsewhere 34 .…”
Section: Discussionsupporting
confidence: 64%
“…Our analysis run was based on the 2016_01_28 data run and included 368 metastatic SKCM samples. T-cell signature genes shown in previous studies 34 were used for clustering metastatic SKCM samples to T-cell signature high and low groups. For cluster analysis, we applied Ward’s method using the Euclidean distance, and a correlation coefficient was used for genes with the same method.…”
Section: Methodsmentioning
confidence: 99%
“…Concentrations of KYNA in cerebrospinal fluid are substantially increased among subjects with schizophrenia, across many studies ([111–114], meta-analysis in [115]); comparable increases are also found among subjects with bipolar disorder with (but not without) psychosis, and KYNA levels are associated directly with psychotic symptoms in both disorders [105]. Treatment with antipsychotics reduces levels on KYNA, from studies in rodents [116, 117].…”
Section: Resultsmentioning
confidence: 99%
“…A glance at Figure 4 will show that KMO inhibition should result in the following important changes in KP metabolite formation in liver, plasma, brain and/or CSF: (1) accumulation of Kyn; (2) consequent to the increase in this substrate, production of KA by the KAT A and of AA by the kynureninase A reactions is increased; (3) decreased formation of 3-HK; (4) a consequent decrease in production of subsequent metabolites from the main oxidative route, namely 3-HAA, QA and PA and from the transamination arm leading to XA formation by KAT B. These changes, which have important implications for drug development for a variety of disease states, can be seen from published data of the effects of the KMO inhibitors m -nitrobenzoylalanine in rats [181, 182] and mice [183] and 3,4-dimethoxy-N-[4-(3-nitrophenyl)thiazol-2-yl]benzenesulfonamide (Ro-61-8048) in mice [184], and of the effects of targeted deletion of the KMO gene in mice [185, 186]. These changes are desirable for achieving protection against the patho-physiological disturbances encountered in many disease states.…”
Section: The Oxidative or Kynurenine Pathwaymentioning
confidence: 99%